Pengaruh Curah Hujan Rata-rata Tahunan terhadap Indeks Erosi dan Umur Waduk pada DAS Citarum Hulu - Bakhtiar, Bakhtiar; Hadihardaja, Joetata; Hadihardaja, Iwan K. (MEDIA KOMUNIKASI TEKNIK SIPIL, 2013)
The aim of this study is to find out the effect of annual rainfall on the erosion index and the life of a reservoir. The erosion index is defined as the total soil loss divided by the tolerable soil loss. The life of a reservoir is affected by the amount of sediment flowing into the reservoir and sediment trap, which is a function of the effective capacity of the reservoir and the inflowing water. Soil and Water Assessment Tool (SWAT) version 2005 model was incorporated into this study to simulate hydrological processes taking place in the catchment. ArcSWAT (ArcGIS Interface for SWAT 2005) program was used as a preprocessing tool to write in input files to be executed by SWAT.SWAT model involves a great number of parameters. Hence, its reliability depends so much on the data availability and some parameter adjustments. From the calibration and validation results on annual data, the model is considerably of good performance. This was proven from the coefficient of correlation (r), coefficient of determination (R2), model efficiency (ME), and index of agreement (IA) which are close to 1 except for the sediment inflow. The difference between the observed and simulated sediment inflow resulted because the SWAT model accounts for the annual variation in precipitation and mean inflow discharge which is not manifested in the observed data. The modeling results revealed that the average inflowing sediment into the reservoir is 5,102,000 ton/year resulting in 46.18 year effective life of the reservoir which corresponds to the critical degree of 1.15. The graph plotting the values of the sediment inflow and the critical degree of the reservoir life reveals a linear relationship.